THE ROLE OF ACHIEVEMENT ACCOUNTING IN COST MANAGEMENT AND RATIONALIZATION OF OPERATIONAL DECISIONS (AN APPLIED STUDY IN THE STATE COMPANY FOR ELECTRICAL INDUSTRIES) - Adnan AskarAlwan , HaiderTawfeeq Khalil , Hussein Ali Hisab (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The research aims to address the theoretical framework for achievement accounting with an indication of the possibility of its application in economic units in order to manage costs and rationalize operational decisions in a manner consistent with the rapid and successive changes accompanying the modern manufacturing environment. The following hypothesis has been presented: The application of achievement accounting in economic units can help them in managing costs and rationalizing operational decisions. The research sample is the General Company for Electrical Industries, for the data for the fiscal year ending on December 31, 2019. The research reached a set of conclusions, the most important of which are: Accounting for achievement depends on a set of financial and non-financial measures that indicate the ability of the economic unit to achieve achievement within a certain period of time and the amount of the cost it bears in order to achieve that achievement. Completion can help manage cost and streamline operational decisions.